Increasing the Entrepreneurial Independence of Correctional Families through the Development of Degung Arts - Abdullah Ali; Sri Nurhayati; Safuri Musa; Ansori Ansori (JPPM (Jurnal Pendidikan dan Pemberdayaan Masyarakat), 2022)
This study aims to uncover and interpret data about the development of correctional inmates through game art in increasing the entrepreneurial independence of inmates at Class IIA Karawang prison. This research uses a qualitative approach with a case study method. Data collection techniques used include observation, interviews, and literature studies. The research informants consisted of 5 inmates, 1 head of LAPAS, and the supervisor of the LAPAS gamelan art. The results of this study indicate that developing the Degung art of the assisted members in achieving entrepreneurial independence at Class IIA Karawang LAPAS, namely the compatibility between the coaching program and the potential and needs of the assisted residents, while indicators of increasing entrepreneurial independence after participating in Degung art coaching can be seen when the development of Degung art is in progress. In progress, inmates can be more patient in playing gamelan gamelan, agile and follow the supervisor's directions, so that when the term of imprisonment is over, inmates can control themselves more differently than when they first entered prison, the socialization skills of inmates are increasing, and the motivation of entrepreneurship inmates is growing. penitentiary.